Electrochemical magneto-immunoassay for detection of ADAM10 Alzheimer's biomarker using gold nanoparticles as label - de Oliveira, Tássia R.; Manzine, Patricia R.; Cominetti, Márcia R.; Leite, Oldair D.; Faria, Ronaldo C. (Talanta (Oxford), 2024)
Alzheimer's disease (AD), a neurodegenerative and progressive illness with no known cure, is the most frequent cause of dementia in older adults. Dementia in AD is usually preceded by a stage of cognitive decline known as mild cognitive impairment (MCI). MCI has gained attention as an ideal target for prevention and early interventions, considering its reversible characteristic. Here, we propose a magneto-immunoassay based on a low-cost screen-printed electrode for detecting soluble ADAM10 in plasma samples, a potential biomarker for early AD diagnosis. We present a sandwich immunoassay using magnetic beads modified with antibodies to capture ADAM10 from plasma samples and using gold nanoparticles (AuNPs) as an electrochemical label. The assay was designed to accurately detect ADAM10 in diluted plasma with a limit of detection (LoD) of 32.5 pg/mL and a dynamic linear range of 10.0–1000.0 pg/mL. Twenty-three plasma samples from the elderly, including patients with AD, MCI, and healthy subjects (negative control), were analyzed by the magneto-immunoassay and enzyme-linked immunosorbent assay (ELISA), and the ADAM10 levels correlated. This work shows the potential of this protein as a biomarker in the early diagnosis and progression of AD and provides an interesting disposable device with capabilities for applications as point-of-care (PoC) to measure ADAM10 levels. [Display omitted] •A magneto-immunoassay was developed for diagnosis of Alzheimer's disease (AD).•The ADAM 10 biomarker was detected in plasma using a simple screen-printed electrode.•The immunoassay showed capability for early diagnosis of AD.